Temperature controllable optical switch for erbium-doped random fiber laser. (April 2022) - Wu, Di; Tian, Shuang; Zhang, Xiaojuan; Yu, Benli; Ma, Jiajun; Xie, Kang; Cheng, Sheng; Zhang, Junxi; Hu, Zhijia
Highlights: A random fiber laser optical switch with a 36 dB extinction ratio at a wavelength from 1529.00 to 1533.16 nm is obtained at pump power of 60.9 mW when the temperature increases from 60 to 61°C under liquid crystal filled photonic crystal fiber random laser a sensor. We combines the concept of the distributed feedback sensing and point sensing, which makes full use of the Rayleigh scattering feedback and the secondary amplification of EDF to obtain the random lasers. We can use the different clearing temperatures of the LCs to obtain different temperature sensing random fiber lasers optical switches with high extinction ratio. Abstract: Different from the conventional optical switches, a rapid response and simple structure of erbium-doped random fiber laser for optical switch is presented. The random fiber laser (RFL) was achieved by pumping an erbium-doped fiber connected with tens of kilometers of single-mode-fiber (SMF). Meanwhile, the 1 cm-long photonic crystal fiber (PCF) filled with a liquid crystal (LC), which is spliced after the reflected output port of a 980/1550 nm wavelength division multiplexing (WDM) coupler, is used as the sensing unit. A high-extinction ratio more than 36 dB over a wavelength range from 1529.00 nm to 1533.16 nm can be observed when the temperature increases from 60 °C to 61 °C. The high-extinction ratio RFL is caused by the reduction of refractive index of the LC-filled PCF (LCPCF). Under the action of the band gap guiding mechanism, the LC molecules in PCF change from each anisotropic to each isotropic when the temperature increases from 60 °C to 61 °C, which induces thermo-optical switch of the LCPCF. The optical switch of erbium-doped fiber random fiber laser has the best comprehensive performance with low cost, high sensitivity, strong anti-electromagnetic interference ability based on control of the temperature.